Experimental investigation of natural convection in U-shaped thermosyphon - Al-Khawajah, M. F.; Mohamad, Abdulmajeed Abd (My University, 1995)
An experimental apparatus is designed to investigate the thermal performance of U-shaped thermosyphon. The test rig mainly consists of a deep cavity (77 cm in height) with opening at the top. An air baffle is inserted at the middle of the cavity. One of the vertical walls of the cavity is maintained at constant heat flux, while the other vertical wall is exposed to the ambient condition. Connecting walls are insulated thermally. The objective of the work is to gain a fundamental understanding of the natural flow and heat transfer from the mentioned system. Temperature distribution along the heated plate and thermal boundary layer are measured at different locations along the thermosyphon for certain range of parameters (Rayleigh number, geometrical parameters). Experimentally obtained data are compared with data of free convection along isolated flat plate. It is found that the rate of heat transfer at the beginning of the heated plate is higher than the heat transfer from flat plate, but at certain height the rate of heat transfer becomes lower than the rate of heat transfer from isolated flat plate.
Proceedings of the 1995 30th National Heat Transfer Conference. Part 14 --
Keywords: Boundary layers; Heat flux; Temperature distribution; Thermal effects; Thermal insulation; Thermal variables measurement; Wall flow; U shaped thermosyphon; Natural convection